Free Trade Agreements Between the EU and New Zealand and the EU and Australia: An Assessment of Labour Law Provisions - Tyc, Aneta (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
In the first main part of the article, the author researches labour provisions included in the EU–New Zealand free trade agreement (FTA) of 2022. She explains why this FTA shall be perceived as a new, fifth generation FTA and what are the key changes the document offers compared to the fourth generation FTAs, e.g. the EU–Republic of Korea FTA. In her analysis, the author focuses on the possibility of imposing sanctions in the event of a serious violation of fundamental labour rights, as well as on “trade and gender equality” issues. She also highlights areas that need to be improved in future agreements concluded by the EU. In the second main part of the article, the author refers to the EU–Australia FTA, which is still under negotiation at the time of writing. She investigates the main factors influencing the bargaining process and pays attention to some of the most contentious issues between the EU and Australia.